Unusual Cemento-Osseous Dysplasia in the Maxilla: A Case Report - Zahra Jahanshahiafshar; Alireza Babaei; Maryam Seyedmajidi; Maryam Johari (Mashhad University of Medical Sciences, 2022)
Introduction: Cemento-osseous dysplasia (COD) is a reactional fibro-osseous lesion that arises in the tooth-bearing area of the jaw bones, mostly the mandible of middle-aged women. Histologically, COD shows a cellular connective tissue stroma with islands of woven or lamellar bone and cementum-like calcifications. Clinically, these lesions are usually asymptomatic and the related teeth are vital; therefore, they are diagnosed through routine radiographic examinations. Radiographic features of COD are widely variable from completely radiolucent to mostly radiopaque patterns, based on the lesion's stage of maturation.Case report: This case report presents a 60-year-old female with a COD in the first premolar and canine area of the left upper jaw which is a rare region for the occurrence of COD. The lesion has gradually grown to its present size. In contrast to most reported CODs, the current patient was symptomatic. She presented tooth pain due to the remaining roots of tooth #12 (universal system). Moreover, bone expansion and thinning of the buccal cortical plate were obvious in the affected area. After intraoral radiography and cone beam computed tomography (CBCT) examination, removal surgery of the lesion and the remaining roots of tooth #12 was carried out. A histological examination confirmed the diagnosis of COD. The patient was followed for three months and no recurrence and infection were detected.Conclusion: COD lesions have variable clinical and radiologic features. Diagnosis is based on clinical knowledge, radiologic features, and histopathological examination of the lesion. CBCT could help indicate the extension of lesions.